Procesos de empoderamiento de mujeres : subjetivación y transformaciones en las relaciones de poder (2014)
ABSTARCT: The research which serve as basis for this paper studies transformations in power relationships in intimate and community spheres derived from the participation of four women in empowerment processes in the municipalities association called Área Metropolitana del Valle de Aburrá (Medellín-Colombia). The method used was the biographical approach, the results showed that such processes of empowerment constituted subjectivation forms through which the interviewed women went from being passive receivers of other’s power, because of indifference, lack of knowledge and recognition, to legitimize themselves as subjects who work and influence its intimate and community spheres.